On the analysis of the fractal basins of escape in the N‐body ring problem. Issue 6 (12th November 2020) - Navarro, Juan F.; Martínez‐Belda, M. C.
Abstract: This article summarizes the results of a numerical investigation of the phenomenon of escape in the N ‐body ring configuration, focusing on the scenarios that result for N  = 5,  6,  7,  8 peripheral bodies. There is a critical value of the Jacobi constant of the system such that for smaller values, the potential well opens and test particles may leave the potential through any of its N openings. By means of a surface of section, we show the results of the computation of the basins of escape towards the different directions of escape, analyzing the structures that appear in them.